Effect of Managerial Ability and Effectivity on Tenant Business Performance at YARSI University Business Incubator - Suyana, SE. MM., Hilma; Budiman, Andika Nuraga; Nurhayati, Ely (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2023)
The purpose of this study is to explain the importance of tenant performance in the creation of new entrepreneurs/tenants in higher education by entrepreneurship educational institutions where incubators are present. In Indonesia, a number of incubators are emerging, particularly at universities, as places to develop intellectual and professional human resources. The poor performance of the Yarsi University Incubator's tenants can be seen by looking at the 28 tenants that have started operating in the past five months. Because the population and sample for this study were childcare facilities with a total of 28 tenants, this sample was included in a saturated sample. This study discusses the role of tenant performance in the Yarsi University incubator as seen through tenant management skills and tenant effectiveness in operating the business in the incubator. Operative in performing management functions and consists of the ability to plan, organize, direct or perform tasks, and exercise supervision. Effectiveness can now be measured by the outputs and inputs that tenants provide to entrepreneurship in the incubator.